Chronic Obstructive Pulmonary Disease in Women - Louis Laviolette; Yves Lacasse; Mariève Doucet; Miriam Lacasse; Karine Marquis; Didier Saey; Pierre Leblanc; François Maltais (Canadian Respiratory Journal)
BACKGROUND: Little is known about the comparative impact of chronic obstructive pulmonary disease (COPD) between women and men and about women’s response to pulmonary rehabilitation.